An uncertain elite: Professional differences and similarities between engineers and tech workers in times of digital transformation - Martin Krzywdzinski; Sabine Pfeiffer; Martin Kuhlmann; Mario Ottaiano; Michael Heinlein; Tobias Ritter; Judith Neumer; Norbert Huchler (Work Organisation, Labour & Globalisation, 2025)
The digital transformation of industries has given rise to new categories of tech workers, such as software engineers and UX/UI designers, who now work alongside traditional engineers. This study explores the evolving relationship between these groups, focusing on work processes, status perceptions and professional interactions. The research questions addressed include: how has digitalisation affected these two groups' work processes? what strategies do they use to maintain or improve their career paths? and how do their roles converge or diverge? Using qualitative data from interviews and workshops in a German automotive company undergoing a digital and electric mobility transformation, the study finds both competition and cooperation between engineers and IT professionals, with the former adopting some IT work methods and the latter adjusting to the highly structured processes of the industrial sector. Despite growing overlaps, distinct professional identities nevertheless remain.
Keywords: 330; digitalisation; sociology of professions; automotive industry; engineers; data science